1984
DOI: 10.1007/bf00180336
|View full text |Cite
|
Sign up to set email alerts
|

Primordial matter in the outer solar system: A study of its chemical composition from remote spectroscopic analysis

Abstract: Our knowledge of the primordial matter from the objects of the outer solar system has made a considerable progress over the past years, in spite of the lack of any in situ measurements of these objects at the present time. The recent progress of ground-based instrumentation and the launch of the two Voyager fly-by missions have provided a huge amount of new informations about the origin and the evolution of the 'primitive' Solar System objects.The most significant discoveries concerning the atmospheres of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…The ease with which organics could be produced under "natural" conditions suggested that they should be widespread in the cosmos. This was confirmed by direct observation of nonbiological organic material, first in carbonaceous meteorites (Kvenvolden et al, 1970) and then in the interstellar medium Knacke, 1989), comets (Kissel andKrueger, 1987), and the surfaces and atmospheres of the planets and moons of the outer solar system -particularly Titan (Encrenaz, 1984;Sagan et al, 1984;Cruikshank, 1987).…”
Section: Terrestrial Theoriesmentioning
confidence: 65%
“…The ease with which organics could be produced under "natural" conditions suggested that they should be widespread in the cosmos. This was confirmed by direct observation of nonbiological organic material, first in carbonaceous meteorites (Kvenvolden et al, 1970) and then in the interstellar medium Knacke, 1989), comets (Kissel andKrueger, 1987), and the surfaces and atmospheres of the planets and moons of the outer solar system -particularly Titan (Encrenaz, 1984;Sagan et al, 1984;Cruikshank, 1987).…”
Section: Terrestrial Theoriesmentioning
confidence: 65%
“…Comparison of the isotopic composition of the sun and the planets occupies an important place in the study of the origin and evolution of the solar system. This has been reviewed in detail by Encrenaz [1984] for D; the significance of the isotopic composition of N in different bodies in and outside the solar system has been reviewed by Geiss and Bochslet [1982].…”
Section: Isotopic Abundancesmentioning
confidence: 99%
“…The escape may be due to one of the nonthermal processes (see section 3.2) [Brinkmann, 1971;McElroy et al 1976Wallis, 1978;Dalgarno, 1980, 1983 The three elements for which isotopes have been observed (followed by the isotopes in parentheses) are H (D), C (•3C), and N (•SN). Many of these observations have been reviewed recently by Encrenaz [1984]. The importance of knowledge of the isotopic composition of their atmospheres has been emphasized by Gautier and Owen [1983a, b].…”
Section: Marsmentioning
confidence: 99%
See 2 more Smart Citations